Le milieu du jeu vidéo est-il indécrottablement discriminatoire? - Baillargeon, Stéphane (Le Devoir, 2020)
Le mouvement #MoiAussi frappe l’industrie de la manette et son sexisme systémique.
Keywords: Bibliographie; Nettoyer

La musique québécoise à l'ère de #MeToo | UQAM (2020)
La musicologue Vanessa Blais-Tremblay analyse l’évolution des chansons évoquant des violences à caractère sexuel.
Section: Recherche

Comme une «gifle» au visage des victimes - Pineda, Améli (Le Devoir, 2020)
L’action collective des Courageuses contre Gilbert Rozon a finalement été rejetée par le plus haut tribunal du pays.

Il n'y aura pas d'action collective contre l’ex-producteur Gilbert Rozon - ICI.Radio-Canada.ca, Zone Justice et faits divers- (Radio-Canada, 2020)
La Cour suprême rejette l’appel du groupe Les Courageuses, qui souhaitait entreprendre un tel recours.
Publisher: Radio-Canada.ca

Les Courageuses déboutées: « C’est d’une injustice incroyable » - Perron, Louis-Samuel (La Presse, 2020)
« C’est d’une injustice incroyable », lâche Anne-Marie Charette, sous le choc. Comme ses sœurs d’armes, la membre du collectif « Les Courageuses » digère mal le refus de la Cour suprême d’entendre leur appel pour autoriser une action collective contre Gilbert Rozon. Mais pas question de « baisser les bras », assure-t-elle.

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

Politique de prévention du harcèlement psychologique ou sexuel au travail et traitement des plaintes - Théâtre de la Ligue Nationale d'Improvisation (2020)
Keywords: Bibliographie; Nettoyer

Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant) - Service correctionnel Canada (2020)
Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant)
Last Modified: 2023-08-03
Keywords: Bibliographie; Nettoyer

Milieu littéraire : le harcèlement touche une écrivaine sur trois - UNEQ (union des écrivaines et des écrivains québécois, 2020)
L’Union des écrivaines et des écrivains québécois (UNEQ) révèle les résultats d’une enquête menée auprès des autrices et auteurs québécois début octobre. Ces chiffres démontrent sans équivoque le déséquilibre du rapport de force entre les partenaires du milieu, déséquilibre qui mène bien souvent à des comportements inacceptables et à une omerta intolérable.
Keywords: Bibliographie; Nettoyer

#MeToo in Sweden: Museum Collections, Digital Archiving and Hashtag Visuality - Uimonen, Paula (Ethnos, 2020)
In October 2017, the Nordic Museum in Stockholm launched its #metoo collection. The aim was to capture the viral #MeToo campaign that in Sweden has been likened to a (feminist) revolution. Based on archival research, interviews and media analysis, this article explores public submissions to the #metoo collection and analyses the museum’s rationale for collecting what is considered to be difficult cultural heritage. Noting the absence of images in the collection, the article argues that the iconic hashtag #MeToo constitutes an alternative form of digital visuality, here termed hashtag visuality. Hashtag visuality, the article suggests, is an emerging form of visual representation that captures the multimodal logic of social media, blurring distinctions between texts and images. In Sweden, #MeToo hashtag visuality reveals the contradictory prevalence of structural sexism and sexual violence in a country with a national self-image of gender equality and a self-proclaimed feminist government, while affirming feminist agency.
Publisher: Routledge _eprint: https://doi.org/10.1080/00141844.2019.1640264
Keywords: Digital cultural heritage; Myriam; feminist agency; online testimonies; sexual violence; viral campaign

Michel Brûlé reconnu coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2020)
L’éditeur Michel Brûlé a été reconnu coupable mercredi d’agression sexuelle à l’endroit d’une auteure venue le rencontrer pour présenter un manuscrit.
Keywords: Bibliographie; Nettoyer

Patriarchal pits: the gendered experiences of female concert photographers - Lough, Kyser (Journal of Gender Studies, 2020)
While the presence of women in photojournalism is increasing, the way they are treated by their male counterparts remains unbalanced. Drawing from feminist theory and embodiment, this study examines how the gendered experience plays out for women in a particular niche of photojournalism; concert photography. The restricted access of the music scene and the embodied nature of photojournalism combine to present unique barriers for women. In-depth interviews with male and female concert photographers show women still face a form of patriarchal oppression in the field. This is seen through gendered language, such as ‘one of the guys’ versus a ‘mom in the pit’, embodied actions such as direct sexual harassment or indirect benevolent sexism, and in how women are questioned when they identify themselves as a photographer.
Publisher: Routledge _eprint: https://doi.org/10.1080/09589236.2020.1821178
Keywords: Bibliographie; Myriam; Nettoyer; Photojournalism; concert photography; embodiment; feminist theory

Raport de recherche de l'enquête pièces : violences sexuelles en milieu collégial au Québec - Bergeron, Manon; Gagnon, Audréanne; Blackburn, Marie-Ève; M-Lavoie, Dominique; Paré, Caroline; Roy, Sophie; Szabo, Andrea; Bourget, Claudie (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur, Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Nettoyer

Recommandations - Rudesse (Facebook, 2020)
Keywords: Bibliographie; Dans le rapport; Sophie-Anne

Webinaire contre le harcèlement et les violences (milieu cirque) pour artistes & travailleuses/eurs (2020)
En partenariat avec Juripop, En Piste vous présente le webinaire qui fût présenté dans le cadre de sa clinique contre le harcèlement et les violences dans le milieu cirque, qui a eu lieu le mardi 25 août 2020. Ce webinaire présente les services du Centre d'aide aux victimes d'actes criminels (CAVAC) et du Groupe d'aide et d'information sur le harcèlement sexuel au travail (GAIHST). Pour plus d'information et de ressources, visitez notre site web : www.enpiste.qc.ca
Keywords: Bibliographie; Nettoyer; À ajouter

Vague de dénonciations : au tour du cirque de faire son examen de conscience - Siag, Jean (La Presse, 2020)
Depuis quelques semaines déjà, les témoignages de violences sexuelles dans le monde du cirque se multiplient sur les réseaux sociaux. Au point où le regroupement national des arts du cirque, En Piste, a décidé de lancer dès mardi avec Juripop une clinique « contre le harcèlement et les violences dans le milieu du cirque ». La Presse a parlé aux instigateurs de Victims_Voices_Circus, espace virtuel où la parole de nombreuses artistes s’est fait entendre.
Keywords: Bibliographie; Nettoyer

Allégations d'agressions sexuelles : Julien Lacroix rayé des nominations aux Gémeaux (Radio-Canada.ca, 2020)
Le jeune humoriste a récemment fait l'objet d'allégations d’agressions et d’inconduites sexuelles.

Milieu de l’édition sain et prévention du harcèlement - Association nationale des éditeurs de livres/Québec Édition (2020)
L’ANEL représente des maisons d’édition de langue française du Québec et du Canada. Québec Édition est dédié au rayonnement international du livre québécois et franco-canadien.

Julien Lacroix visé par des allégations d’agressions et d’inconduites sexuelles - Pineda, Améli (Le Devoir, 2020)
Neuf femmes racontent avoir été victimes d'agressions ou d'inconduites sexuelles de la part de l'humoriste et comédien.
Keywords: Bibliographie; Nettoyer

Harcèlement à Ubisoft : la joueuse professionnelle Stéphanie Harvey témoigne - Agence France-Presse (Radio-Canada, 2020)
Une vague de dénonciations secoue Ubisoft et l'industrie du jeu vidéo depuis quelques semaines.
Keywords: Bibliographie; Nettoyer

Me Too: The Effects of Sexual Harassment and Assault in the Entertainment Industry - Gaal, Cassandra (Backstage Pass, 2020)
Keywords: Entertainment Industry; Myriam

Simple Plan renvoie son bassiste de tournée suite à des allégations d’inconduites sexuelles contre lui - Bibeault, Matt (99scenes, 2020)
C’est la firme de management de Simple Plan, Coalition Music, qui a confirmé la nouvelle. Chady Awad avait justement remplacé David Desrosiers lorsque ce dernier avait pris une pause de SP pour traiter sa dépression de 2017 à 2019. Awad était également photographe et vidéaste pour Simple Plan. Simple Plan a mis fin à sa... View Article
Keywords: Bibliographie; Nettoyer

Des violences sexuelles et des abus de pouvoir dénoncés dans le milieu littéraire - ICI.Radio-Canada.ca, Zone Arts- (Radio-Canada, 2020)
Un groupe de 300 personnes s’est créé pour que les victimes témoignent et pour exprimer des revendications.
Publisher: Radio-Canada.ca

Le milieu littéraire ébranlé par le mouvement de dénonciations - Lapointe, Josée (La Presse, 2020)
Le milieu littéraire fait face lui aussi au mouvement de dénonciations lancé il y a une dizaine de jours. Un groupe de 300 autrices et actrices de la chaîne du livre s’est formé de manière privée pour échanger à propos de cas d’inconduites sexuelles dont beaucoup ont été victimes.
Keywords: Bibliographie; Nettoyer

Violences sexuelles et abus de pouvoir dans le milieu littéraire : il est plus que temps d’agir - UNEQ (Union des écrivaines et des écrivains québécois, 2020)
L’UNEQ donne son appui à la lettre rédigée par un groupe constitué de plusieurs centaines de femmes et minorités de genre déterminées à faire cesser une situation qui ne peut plus durer dans le milieu littéraire.
Keywords: Bibliographie; Nettoyer

Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Cole, Alayna; Zammit, Jessica (CRC Press, 2020)
Description Cooperative Gaming provides context and practical advice regarding diversity in the games industry. The book begins with a deep dive into research literature and the history of diversity in the games industry to provide context around what diversity is and why it is a topic worth considering. The book looks at the different facets of diversity and games, exploring the issues and solutions within game development, studio management, event planning, and more. It provides people with practical advice about being a marginalized person in the games industry and how to be heard, how studios can support inclusive practices, and events can actively become more accessible to a diverse audience. Key Features • Explores the history of diversity in games • Provides important information around what it is like to be a marginalized person in the industry • Gives practical steps to improve the inclusivity of the industry that are designed to aid in contextualizing and upskilling new developers Author Bios Alayna Cole is the managing director of Queerly Represent Me, a not-for-profit championing queer representation in games. Alayna is also a producer at Sledgehammer Games, co-chair of the IGDA LGBTQ+ special interest group, and an award-winning games journalist and game developer. She was featured on the 2016 and 2017 Develop Pacific 30 Under 30 lists and the 2017 and 2019 Develop Pacific Women in Games lists, and she has received several other accolades in the industry. Jessica Zammit started writing in 2013 for Start Select Media, and for the next five years she followed her interest in writing about representations of mental health, diversity, and particularly, sexuality in video games. Jessica has been speaking about diversity in games at conventions such as PAX Australia since 2016 and has been featured on several other discussions in and around the topic of representation in games and games criticism. Along with her co-author, she is co-chair of the IGDA LGBTQ+ special interest group, and she was featured on the 2018 Develop Pacific 30 Under 30 and Women in Games lists.
Google-Books-ID: 0XjtDwAAQBAJ
Keywords: Computers / Programming / Games; Irina

Inconduite sexuelle: deux acteurs largués - Gendron-Martin, Raphaël (Le Journal de Montréal, 2020)
La valse des dénonciations pour inconduite sexuelle touchant le milieu culturel se poursuit.
Keywords: Bibliographie; Nettoyer

Vague de dénonciations: des têtes tombent dans le milieu artistique - Bélanger, Cédric (Le Journal de Québec, 2020)
Les dénonciations font tomber Maripier Morin, Bernard Adamus et le patron de Dare To Care.
Keywords: Bibliographie; Nettoyer

Quand se taire n’est plus une option - Papineau, Philippe; Renaud, Philippe (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Safia Nolin accuse, Maripier Morin s’excuse - Groguhé, Marissa (La Presse, 2020)
L’auteure-compositrice-interprète Safia Nolin a provoqué une onde de choc en accusant mardi Maripier Morin de s’être livrée à du harcèlement sexuel, d’avoir commis une agression physique et d’avoir proféré des propos racistes lors d’une soirée dans un bar il y a deux ans. Des allégations en partie admises par l’animatrice télé, qui a présenté ses excuses le lendemain.
Keywords: Bibliographie; Nettoyer

#ThisIsArtSchool Is Exposing Allegations Of Racism & Sexual Abuse In Montreal Universities - Elliot, Teddy (MTL Blog, 2020)
As stories of racism and discrimination towards Black, Indigenous, and people of colour continue to dominate public discourse, more and more shocking allegations come to light about the lived experiences of systemic racism.
Keywords: Bibliographie; Nettoyer

'Urban' no more: black British music execs call for industry reforms (the Guardian, 2020)
Open letter from new group seeks action on racism and better career development
Section: Music

‘To draw light, you need shadow’: Using graphic art to counter gender based violence in Drawing the Line - Zare, Bonnie (South Asian Popular Culture, 2020)
Women in India cope with an ongoing sense of precarity owing to the frequency of street harassment and sexual violence; this impacts their freedom to travel and sense of autonomous agency. The December 2012 Nirbhaya case, the rape and fatal injury of a Delhi medical student, returned the subject of rape to public discourse leading to mass protests and, eventually, some stronger anti-rape laws; however, #metoo allegations surface weekly, and artists and activists are demanding that the trivialization of rape and verbal abuse stop and active steps be taken to dismantle the cultural scaffolding undergirding twomen's violation. In 2014 a collaboration by Zubaan Press (New Delhi) and the Goethe Institute (Germany) brought a group of Indian graphic artists together to create stories about women’s ground realities and the microaggressions they experience. The resulting publication, Drawing the Line: Indian Women Fight Back, contains fourteen vignettes which reveal the constraints women experience and also illuminate women’s capacity for resilience and boldness. This essay analyzes the forms of resistance imagined in these narratives, how particular stories illuminate slow violence, and what may be lost if we know little about the perpetrators who commit these acts against women.
Publisher: Routledge _eprint: https://doi.org/10.1080/14746689.2020.1775342
Keywords: Essay; India; Indian women; Myriam; Sexual harassment; Gender; graphic novel; sexuality; violence

Contemporary Feminist Protest in Ireland: #MeToo in Irish Theatre - Fitzpatrick, Lisa (Irish University Review, 2020)
This essay draws upon the work of Judith Butler, Sara Ahmed, and Germaine Greer to consider the #MeToo movement and its reflection in the work of the author's students and the scandal at Dublin's G...
Publisher: Edinburgh University Press
Keywords: #MeToo; Bibliographie; Contemporary Feminism; Intergenerational; Intersectional; Nettoyer; Raphaël; Teaching

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : une recherche en travail social féministe - Robert Durand, Catherine (2020)
L’improvisation théâtrale est une discipline artistique qui est grandement pratiquée, et ce, au Québec comme dans le monde. De manière implicite et explicite, l’une des réflexions qui revient souvent dans ce milieu est celle de la place différente qu’y occupent les femmes en comparaison avec celle de leurs collègues masculins. Les improvisatrices constatent qu’elles ont une place souvent minoritaire, rappelant les inégalités qui se présentent aussi en société pour les femmes. Ce constat n’est pas nouveau mais puisque très peu de recherches portent sur l’improvisation théâtrale, cette question n’a jamais vraiment été explorée. Ce mémoire pose donc les questions de recherche suivantes : Quelle est la place particulière des femmes dans ce milieu ? Quels inégalités et stéréotypes de genre ce milieu véhicule-t-il ? Et, comment les improvisatrices ont-elles le potentiel d’agir sur ces inégalités de genre et de défaire les stéréotypes ? Les objectifs de recherche sont : 1) Recueillir le point de vue des improvisatrices au sujet de leur pratique ; 2) Comprendre la situation particulière des femmes dans ce milieu ; 3) Identifier les stéréotypes et les inégalités de genre véhiculés en improvisation théâtrale ; 4) Relier ces stéréotypes et inégalités de genre à ceux véhiculés en société. Le cadre théorique de ce mémoire est celui du travail social féministe qui s’intéresse notamment aux oppressions et inégalités vécues par les femmes au quotidien, dans « l’ordinaire » de leur vie, ce dont la pratique de l’improvisation théâtrale fait partie. Ancrée dans une méthodologie féministe et qualitative, 8 entretiens semi-dirigés ont été réalisées. L’analyse et la discussion de ces résultats a mis de l’avant l’idée que l’improvisation théâtrale est un espace de reproduction de la socialisation genrée mais aussi un lieu de résistances et donc, plus globalement de négociation entre ces deux pôles. En conclusion, sont soulignés certains nœuds féministes de la recherche et des pistes de solutions pour y pallier. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Féminisme, Improvisation théâtrale, Socialisation genrée, Stéréotypes de genre, Résistances, Recherche féministe, Travail social féministe.
Place: Montréal (Québec, Canada) Publisher: Université du Québec à Montréal

Mobilisations féministes sur Facebook et Twitter: Le cas du mouvement #StopCultureDuViol au Québec - Hübner, Lena A.; Pilote, Anne-Marie (Terminal, 2020)

Comedy in the Era of #MeToo: Masking and Unmasking Sexual Misconduct in Stand-Up Comedy - Oppliger, Patrice; Mears, Kathryn (The Dark Side of Stand-Up Comedy, 2020)
With the announcement of allegations of sexual harassment and sexual assault against beloved comedians, we ask, “Can one separate the art from the artist?” Comedians are supposed to bring audiences joy and laughter; however, this role is challenged when there is incongruity between the comic persona and the real-life misdeeds of comedians. We explore the rise of the #MeToo movement and the role of comedy in exposing as well as masking allegations against Bill Cosby, Louis C.K., Al Franken, and Aziz Ansari. Guided by disposition theory and disengagement models, findings reveal factors of race, gender, and personal relationships appear to influence comedians’ assessment of fellow comedians accused of sexual misconduct. Audience members also appear to experience moral disengagement.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Louis C.K.’s time’s up time out: rereading persona post-scandal - Piper, Melanie (Celebrity Studies, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics

Non-Consensual Sexual Contact at Electronic Dance Music Parties - Palamar, Joseph J.; Griffin, Marybec (Archives of Sexual Behavior, 2020)
Non-consensual sexual contact in bars is common, but few studies have focused on the extent of this problem at electronic dance music (EDM) parties, which are growing in popularity. We aimed to estimate prevalence and correlates of non-consensual sexual contact among individuals who attend EDM parties in New York City (NYC). Adults (ages 18–40 years) entering EDM parties in NYC were surveyed in 2018 using time–space sampling. Participants (n = 1005) were asked whether they had experienced unwanted or uninvited sexual contact including unwanted groping, kissing, or touching at an EDM party. We estimate that 15.2% of EDM party attendees in NYC have experienced non-consensual sexual contact at such parties. The majority (62.5%) of those reported that it occurred 1–2 times and 49.1% were usually or always drunk or high during the encounter(s). Almost all women experiencing non-consensual contact (99.5%) were all or mostly touched by men; 38.6% of men were all or mostly touched by other men. Women were at more than twice the odds of reporting non-consensual sexual contact than men (aOR = 2.38, p < .05) with 21.8% of women reporting experiencing non-consensual sexual contact compared to 11.0% of men. Among women, those ages 18–24 were at over twice the odds (aOR = 2.75, p < .05) of experiencing non-consensual sexual contact than those ages 25–40. EDM party environments can increase susceptibility to non-consensual sexual contact. Prevention needs to be geared toward those at risk, and education is needed for those likely to commit non-consensual sexual contact.
Keywords: Dance music; Drug use; Non-consensual sex; Sexual assault

Gendered Violence at International Festivals: An Interdisciplinary Perspective - Platt, Louise; Finkel, Rebecca (Routledge, 2020)
Gendered Violence at International Festivals is a groundbreaking collection that focusses on this highly important social issue for the first time. Including a diverse range of interdisciplinary studies on the issue, the book contests the widely held notion that festivals are temporal spaces free from structural sexism, inequalities or gender power dynamics. Rather, they are spaces where these concerns are enhanced and enacted more freely and where the experiential environment is used as an excuse or as an opportunity to victim blame and shame. In this emerging and under-researched area, the chapters not only present original work in terms of topics but also in theoretical and methodological approaches. All of the chapters are cross- or interdisciplinary, drawing on gender, sexualities, cultural and ethnicity studies. Studies from a range of highly regarded academics based around the world examine the subject by looking at examples from a wide range of destinations, including Spain, Argentina, Nigeria, Zimbabwe, Australia, Canada and the UK. This significant book progresses understanding and debates about gendered festival experiences and emphasises the symbolic and physical violence often associated with them. This will be of great interest to, undergraduate and postgraduate students and academics in the field of Events Studies. It will also be of use to practitioners or non-profit workers in the festival industries, including festival management organisations and planning committees.
Google-Books-ID: Q6bYDwAAQBAJ
Keywords: Business & Economics / Industries / Hospitality; Travel & Tourism

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

#metoo 2.0 to #meNOmore: Analysing Western Reporting About Sexual Violence in the Music Industry - Baker, Andrea; Williams, Katrina; Rodrigues, Usha M. (Journalism Practice, 2020)
In October 2017, #metoo 2.0 reinforces the gendered sexual violence in the creative sector [Marghitu, 2018. “It’s Just art: Auteur Apologism in the Post-Weinstein era”, Feminist Media Studies, 18(93): 491–494] Building on this movement, on 11 November that year, 2912 women “testified about the situation in the Swedish music industry”, signing an open letter condemning sexual violence [Nyheter, 2017. “2192 Women in the Swedish Music Industry Behind Appeal Against Sexism.” Dagens Nyheter, November 17. https://www.dn.se/kultur-noje/2192-women-in-the-swedish-music-industry-behind-appeal-against-sexism/]. After the Swedish initiative, on 12 December 2017, the #meNOmore hashtag was established by 1000 women who signed an open letter to the Australian music industry speaking out against similar behaviour [Whyte, 2017a. “Artists Speak Out Against Sexual Harassment in the Music Industry.” AM – ABC Radio, December 13. https://www.abc.net.au/radio/programs/am/sexual-harassment-in-the-music-industry/9253956]. Using a content analysis framework, this study examines the media framing of 26 stories about #meNOmore by the Western press from 22 November 2017 (height of the Swedish campaign) to 21 December 2017 (a week after the hashtag surfaced in Australia). Research from journalism studies and musicology highlights that sexual violence is historically engrained in the media and music industries. However, findings from our study of the first month’s coverage of the #meNOmore content analysis in 2017 reveal that media reports about women and sexual violence were framed around addressing gender inequality and systemic structural issues in the music industry. This raises the question, has the media has turned a corner when covering sexual violence in the post #metoo era?
Keywords: Bibliographie; Nettoyer

La Cour d’appel donne raison à Gilbert Rozon - Corriveau, Jeanne (Le Devoir, 2020)
Le tribunal a annulé l’autorisation de l’action collective des Courageuses contre l’ancien magnat de l’humour.
Keywords: Bibliographie; Nettoyer

“These things happen”: Hashtag activism and sexual harassment in the South African film and television industries - Paleker, Gairoonisa (Agenda, 2020)
In August 2017, the South African advocacy group Sisters Working in Film and Television (SWIFT) launched the #ThatsNotOk campaign, which has to date produced six episodes of short films (one episode in two parts, making it seven in total) elucidating the different forms sexual harassment takes, and the different scenarios in which it occurs, in the South African film and television industries. This profile engages with SWIFT and the Public Service Announcement (PSA) films as discursive sites and texts respectively, and provides textual analyses of the PSAs in the context of digital feminism and feminist activism against sexual harassment in the film and television industries. The profile motivates that as expressions of digital feminism, the PSAs critique the pervasiveness and normalisation of sexual harassment, while failing to engage with or critique the neoliberal logic and structure of the film and television industries.
Publisher: Routledge _eprint: https://doi.org/10.1080/10130950.2020.1720162
Keywords: #ThatsNotOk; Irina; South African film and television; digital feminism; hashtag activism

Unwanted Sexual Attention in the Night-Time Economy: Behaviors, Safety Strategies, and Conceptualizing “Feisty Femininity” - Gunby, Clare; Carline, Anna; Taylor, Stuart; Gosling, Helena (Feminist Criminology, 2020)
Almost nothing is known about ?unwanted sexual attention? and women?s navigation of it when in bars and nightclubs. Using focus group discussions, this article addresses that gap. It develops knowledge of the behaviors that constitute unwanted, the safety strategies used to manage them, and examines how these practices underpin gender performance in night-time spaces: environments renowned for the dilemmas they pose to women. We then use these data to develop the concept ?feisty femininity? to highlight a neglected form of femininity that overtly resists unwanted encounters. This femininity can arguably play a role in efforts aimed at ending gendered violence.
Publisher: SAGE Publications

Aide aux Trans du Québec (Aide aux Trans du Québec, 2020)
Ligne d’écoute et de référenceSans frais : 1 (855) 909-9038, poste 1Nous écrireGroupes de soutien hebdomadaires sur ZoomPour et par les personnes trans, non binaires et en questionnement.Nos services Diapositive précédente Diapositive suivante Notre mission Les buts principaux de l’ATQ sont d’apporter de l’aide et de briser l’isolement des personnes trans, non-binaires et en questionnement. […]
Keywords: Coffre à outils; À ajouter

Entente collective entre l'Union des artistes et l'Association québécoise de la production médiatique (Artistes interprètes) (2020)
Keywords: Bibliographie; Nettoyer

Best Practices for scenes involving nudity, intimacy, simulated sex and sexual violence - ACTRA (2020)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Land acknowledgment et Equality statement - ACTRA (2020)

Des violences sexuelles et des abus de pouvoir dénoncés dans le milieu littéraire - Bourel, Fanny (Radio-Canada, 2020)
Un groupe de 300 personnes s’est créé pour que les victimes témoignent et pour exprimer des revendications.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Le jour où Éric Salvail est tombé - Bourgault-Côté, Guillaume (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Expériences de comportements sexualisés inappropriés, d’agressions sexuelles et de discrimination fondée sur le genre vécues par les travailleurs dans les provinces canadiennes, 2020 - Burczycka, Marta (Statistique Canada, 2020)
Keywords: Bibliographie; Nettoyer

‘Put some balls on that woman’: Gendered repertoires of inequality in screen composers’ careers - Cannizzo, Fabian; Strong, Catherine (Gender, Work & Organization, 2020)
This study contributes to debates about gendered career outcomes in the creative industries using data collected in interviews with Australian screen composers. We identify how gendered inequalities are legitimated through professional norms by comparing the responses of screen composers on barriers to women’s advancement. The article explores how three distinct interpretive repertoires help reproduce the gender inequality regime present in the screen composition field. These repertoires are ‘art vs. equality’, where working towards equality can be framed as antithetical to artistic ideals; ‘gendered music’, where men and women are posited as making fundamentally different types of music; and ‘confidence’, where men are framed as innately possessing certain entrepreneurial skills vital to success in the creative industries, while women both shoulder the blame for not possessing such skills and recognize the risks inherent for them in performing confidence. By focusing on repertoires, this study describes the means by which gender-based discrimination is made overt and offered justification among screen composers, posing challenges to organizations and individuals seeking to address gender inequality in the profession.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12496
Keywords: Australia; Musique de film; Myriam; composers; creative industries; cultural industries; gender inequality; sexism

La musique québécoise à l'ère de #MeToo - Caza, Pierre-Etienne (Actualités UQÀM, 2020)
La musicologue Vanessa Blais-Tremblay analyse l’évolution des chansons évoquant des violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer

Les personnes victimes d'agressions sexuelles ou de violence conjufale face au système de justice pénale: état de situation - Conseil du statut de la femme (Québec, Conseil du statut de la femme, 2020)

Les personnes victimes d’agressions sexuelles ou de violence conjugale face au système de justice pénale: état de situation - Conseil du statut de la femme (Conseil du statut de la femme, 2020)

Violences sexuelles et abus de pouvoir dans le milieu littéraire: il est plus que temps d’agir - Déclaration commune (Liberté – Art et politique, 2020)
Déclaration commune
Keywords: Bibliographie; Nettoyer

Je n'en ai jamais parlé à personne - Delvaux, Martine (Éditions Heliotrope, 2020)
«En octobre 2017, devant la vague de témoignages suscitée par le mouvement #moiaussi, j’ai senti une urgence : une fois sorties du silence, nous ne devions pas y retourner. C’est la raison pour laquelle j’ai lancé un appel. Ce livre est une chambre d’échos. Un chœur. Sans déesse ni héroïne en tête, des voix avancent. Nous faisons front commun.» Martine Delvaux «Je n'en ai jamais parlé à personne» : paroles recueillies et agencées par Martine Delvaux
Keywords: Bibliographie; Nettoyer

Teaching Tertiary music in the #metoo era - Devenish, Louise; Sun, Cecilia; Hope, Cat; Tomlinson, Vanessa (Tempo, 2020)
Abstract Over the past two decades significant changes in approaches to gender equity have taken place in the fields of contemporary music and music research. However, women in music are still disadvantaged in terms of income, inclusion and professional opportunities. In Australia a national approach to improving gender equity in music has begun to emerge as once-controversial strategies trialled by four tertiary institutions have become established practices. This article discusses successful inclusion strategies for women in music, including the commitment to gender-balanced programming across all concerts at Queensland Conservatorium of Music by 2025, the introduction of mandatory quotas in recital programmes at Monash University, mentoring programmes for women composers at Sydney Conservatorium of Music, and the development of coursework devoted to women in music at The University of Western Australia, as well as other initiatives that have emerged from them, both within and beyond the institution. Each approach is examined in the context of broader global discussions around gender and feminism. The public willingness to engage in discussions over sexual harassment, sexual assault and gender discrimination in the workplace that has resulted from the #MeToo movement is cited as key in influencing the engagement of students and professionals with these strategies and subsequent influence on performance practices, project development and presentational formats in new music.
Keywords: Myriam

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Rapport de recherche sur l'état du milieu du spectacle d'improvisaiton théâtrale au Québec - Garneau, Jocelyn (Le théâtre de la Ligue Nationale d'Improvisation et la Rencontre Théâtre-Ados de Lavac avec l'appui financier du Ministère de la Culture et des Communications du Québec, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Sexual Harassment in the Post-Weinstein World - Grossman, Joanna L. (UC Irvine Law Review, 2020)
Keywords: Myriam; film industry

Sexual violence at live music events: Experiences, responses and prevention - Hill, Rosemary Lucy; Hesmondhalgh, David; Megson, Molly (International Journal of Cultural Studies, 2020)
Recent media reporting has highlighted that incidents of sexual violence frequently occur at live music events. Sexual violence has significant impacts on the health of those who experience it, yet little is known of how it impacts on everyday engagements with music, nor what measures venues and promoters might take to prevent and respond to incidents. Through interviews with concert goers, venue managers, promoters and campaigning groups, we investigated experiences of sexual violence at indie, rock, punk and funk gigs in small venues in one English city. We show that sexual violence at live music events significantly impacts on (predominantly) women’s musical participation. We argue that venues and promoters must work proactively to create musical communities that act as a defence against the normalisation of sexual violence, taking inspiration from safer space policies.
Keywords: Camille; gender; live music; prevention; safe spaces; sexual violence; unwanted sexual attention

Can You Come Back from Being Cancelled? A Case Study of Podcasting, Cancel Culture, and Comedians during #MeToo - Holman, Kylie J. (University of Nebraska, 2020)
Cancel culture is a new phenomenon of public shaming, facilitated by social media. This type of public shaming is accepted due to the alleged transgression of those who are cancelled. Social understanding of cancel culture does not generally allow for redemption. Using the theoretical framework of Feminist Media Studies (Van Zoonen, 1994) and Media Framing Theory (Gitlin, 1980), this study reveals the media’s role and power in the cancelling process. This study utilized a mixed-methods approach of case study and text analysis of episodes from the pop culture and politics podcast, Keep It. The case study focused on podcast episodes pertaining to two comedians cancelled for allegations of sexual misconduct in the #MeToo era [Oct. 2017 – Present]: Aziz Ansari and Louis C.K. The study also provided comparative cases of other comedians and comedic actors who were cancelled. Findings add to our understanding of cancel culture and appropriate methods of redemption for those who are cancelled.
Keywords: #MeToo; Bibliographie; Cancel culture; Comedians; Nettoyer; Podcasting; Redemption; Sophie-Anne

Experiencing Male Dominance in Swedish Film Production - Jansson, Maria; Wallenberg, Louise (Women in the International Film Industry: Policy, Practice and Power, 2020)
Sweden has been hailed for its recent success in increasing the number of female directors, scriptwriters and producers. Published reports, panel discussions and a vast number of press conferences on the pressing matter of gender equality within the industry together with a 5050 quota have all put the Swedish film industry—and its CEO Anna Serner—on the map. However, the last couple of years has disclosed several scandals regarding sexism and discrimination in the Swedish film industry—just as in other national film industries. This paper sets out to discuss how female film workers (e.g., directors, actors and producers) understand and negotiate their experiences of male dominance within their work context. Based on a series of interviews with women working in Swedish film from the early 1960s until today, we analyze similarities and differences in experiences as well as how these experiences are explained by the interviewees. Their stories are analyzed by using feminist institutional theory to understand how policy, funding schemes and other institutional aspects are intertwined with their experiences. The paper sets out to analyze three themes: (1) comments and suggestions during production and post-production regarding female protagonists; (2) experience of gender trouble in the process of fundraising; and (3) strategies used by the interviewed filmmakers to produce a more women-friendly environment during productions.
Keywords: Irina

Faire face au harcèlement en milieu de travail culturel: Un rapport sur les mécanismes de dénonciation et d’enquête existants et potentiels pour travailleurs et employeurs culturels - Labine, Lise; LeSage, Jeanne; Gagnon, Grégoire (Conseil des ressources humaines du secteur culturel, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer

Vague de dénonciations : un groupe de soutien est créé dans le milieu littéraire - Larouche, Katy (Radio-Canada, 2020)
Keywords: Bibliographie; Nettoyer

Women in the International Film Industry: Policy, Practice and Power - Liddy, Susan (Springer International Publishing, 2020)
Keywords: Irina

Identity work in female-led creative businesses - Martin, Lynn; Jerrard, Bob; Wright, Lucy (Gender, Work & Organization, 2020)
This study explores the identity work carried out by three female owner-managers in creative industry businesses, identified in Government reports as a discriminatory industrial sector for women in the UK. Through the development of narratives by the owners and other participants, observation of practice and review of online and offline materials, three cases emerged. These showed overlapping, different identities developed and performed through identity work. Each presented rational and logical persona as business leaders despite observation showing extensive use of intuition and gut feeling in both creative and entrepreneurial aspects of the business. Intuition and gut feeling were seen as inappropriate at work as they belonged to the home sphere, emotionally based and therefore automatically unreliable. While occupying male stereotypes and avoiding the female realm of emotion at work, these women expressed femininity through their emphasis on the maternal, ‘being a good mother' as a desired ideal being embedded in work as well as home practice.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12357
Keywords: Myriam; creative industries; entrepreneurship; gender; identity; innovation

Conceptualising safety and crime at UK music festivals: A gendered analysis - Measham, Hannah King ;, Fiona, Hannah Bows ; (Gendered Violence at International Festivals, 2020)
There has been a global surge in music festivals over the last decade, especially in Europe. In the UK, it is estimated that more than 3.5 million people attended the 230 music festivals in 2015 (Time Out, 2015; UK Festival Awards, 2016). Despite a body of research indicating higher levels of crime, particularly acquisitive and violent crime in spaces with similar characteristics (e.g. nightclubs, pubs and gigs), there have been no previous studies examining the occurrence or nature of crime at music festivals. This chapter brings together conceptual developments across the social sciences to shed light on the underexplored subject of gender and safety at music festivals, a leisure location of growing interest to social scientists and of significant growth within the events industry. This chapter presents data from the first UK study to explore safety and crime at music festivals and raises questions regarding the distinctive features of commercialised music festivals, the extent to which they can be considered transgressive or countercultural spaces and what might be the distinctions, if any, of gendered sexual violence within such spaces.
Num Pages: 18

The most beautiful job in the world: lifting the veil on the fashion industry - Mensitieri, Giulia; Lehrer, Natasha (Bloomsbury Visual Arts, Bloomsbury Publishing Plc, 2020)
Keywords: Fashion; Myriam

De nouveaux gestes déplacés de musiciens dénoncés - Papineau, Philippe (2020)
Keywords: Bibliographie; Nettoyer

Video Games - Pletcher, Isaac (Communication Technology Update and Fundamentals, 2020)
A video game is an interactive digital entertainment that you “play” on some type of electronic device. The medium has existed in some form since the 1950s, and since that time, has become a major worldwide industry, spawning technology battles and being birthed in new iterations that become ubiquitous parts of modern life. This chapter will look at the development of video games from the beginning, through the golden age, and into the era of the console wars. Further, it will point out the enormous revenues video games make, and show how the #metoo movement and unions are working to change the face of the industry.
Num Pages: 12
Keywords: Irina

Ubisoft : les démissions ne viendront pas à bout de la toxicité, disent des employés - Prévost, Hugo (Radio-Canada, 2020)
Le géant du jeu vidéo est plongé dans la tourmente depuis des semaines en raison d'allégations de harcèlement.
Keywords: Bibliographie; Nettoyer

Dénoncer le harcèlement dans le milieu de l'improvisation (D'Est en Est, 2020)
Keywords: Bibliographie; Nettoyer

Cours/Courses - ReadtheCode (2020)
Keywords: Coffre à outils; À ajouter

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : Une recherche en travail social féministe - Robert Durant, Catherine (Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer; Sophie-Anne

Cultural sexism: the politics of feminist rage in the #metoo era - Savigny, Heather (Bristol University Press, 2020)

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

Les expériences des victimes de violence sexuelle dans les programmes de justice réparatrice - Wemmers, Jo-Anne; Parent, Isabelle; Casoni, Dianne; Quirion, Marika Lachance (Centre international de criminologie comparée, 2020)
Keywords: Bibliographie; Expérience; Justice; Nettoyer; Système judiciaire; Victimes; Violence

A Nonbinary Actor Prepares (for Battle) - Woodzick, K. Bylines (Theatre Topics, 2020)
Publisher: Johns Hopkins University Press
Keywords: Bibliographie; Nettoyer; Raphaël

A Single Drop of Water: Vulnerability, Invisibility, and Accountability in South Korean Theatre’s Moment of Crisis - Younghee, Park; Neideck, Jeremy (Performance Paradigm, 2020)
In early 2018, encouraged by the #MeToo movement sweeping the Western media landscape, Korean actor Park Younghee took to Facebook to write of her experiences of sexual harassment at the hands of a prominent theatre director and academic in the 1990s. While Younghee didn’t publicly name her abuser, it was not long before the social media machine identified Oh Tae Suk as the man she alluded to, and his world-renowned Geukdan Mokwha as the site of her abuse. Days later, prolific theatre director Kim Soo-hee made allegations of violence and sexual abuse against Lee Yoon-taek, the artistic director of the juggernaut theatre company Yeonhuidan Georipae, setting off a firestorm in the South Korean Media that has yet to die down. In South Korea, public performances of grief, allyship, and holding the government to account are hallmarks of democratic transformation. In this article, Park Younghee tells parts of her story to longtime collaborator Jeremy Neideck, and they attempt to weave a coherent narrative out of their yearlong discussion about the social, cultural, and political histories of Korea. This article seeks to illuminate, but not necessarily explain, the environments in which men like Lee Youn-taek and Oh Tae Suk were able to perpetrate abuse.
Keywords: Bibliographie; Nettoyer; Raphaël